Implementasi Full Day School dalam Pembentukan Karakter Religius dan Disiplin Siswa Kelas VII SMP Islam Terpadu Al-Ittihad Ciampea Kabupaten Bogor - Revi Khoeril Kholqillah; Muhammad Fahri; Reni Sinta Dewi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Character plays an important role for students, one of the efforts to shape the character of quality students is through full day school so that the formation of these characters can achieve results. The purpose of this research is to describe the implementation of full day school in the formation of religious and disciplinary character of students and to find out what factors become obstacles in the formation of religious and disciplinary character. The method in this study was qualitative with a field study approach (Field Research) and this research was conducted in class VII. Data collection techniques in this study were carried out by triangulating data sources (a combination of observations, interviews and documentation). The informants and informants in this study were school principals, PAI teachers, homeroom teachers for class VII and students. The results of the study stated that full day school can form religious and disciplinary character values ​​by habituation and exemplary methods through programs to strengthen character education in schools, starting from setting intense schedules to varied teaching and learning activities. This can be seen from the teaching and learning process activities that run in an orderly manner, such as Islamic habituation activities. While the main factor that acts as an obstacle is the family, such as busy parents, social environment, and school facilities and infrastructure that are not optimal